Analisis Kata Kunci dan Implementasi SEO On Page Website STMIK YMI Tegal - Nursidik, Maulia (Universitas Pahlawan Tuanku Tambusai, 2025)
This reSearch aims to analyze keywords based on Search volume and implement On Page SEO techniques to improve organic Search performance on the stmik-tegal.ac.id website. Optimization is done by using several SEO analysis tools such as Rank Tracker, Google Keyword Planner, Ahrefs, and manual Search. This research was conducted qualitatively through case studies as the main method of data collection and analysis. The analysis showed that keywords such as campus in Tegal, STMIK campus, and Tegal campus have significant Search volume and high relevance to website content. After the implementation of On Page SEO, there was an increase in keyword ranking in Google Search results as shown by the increase in position from page two to page one within one month. This reSearch provides a strategic contribution for educational institutions in increasing digital visibility and attracting prospective students through organic Search